Risk Factors for Lateral Meniscus Posterior Root Tears in the Anterior Cruciate Ligament–Injured Knee: An Epidemiological Analysis of 3956 Patients From the SANTI Study Group. Issue 3 (March 2019) - Praz, Cesar; Vieira, Thais Dutra; Saithna, Adnan; Rosentiel, Nikolaus; Kandhari, Vikram; Nogueira, Helder; Sonnery-Cottet, Bertrand
Background: Lateral meniscus posterior root tears (LMPRTs) result in loss of hoop forces and significant increases in tibiofemoral contact pressures. Preoperative imaging lacks reliability; therefore, holding an appropriate index of suspicion, based on the epidemiology of and risk factors for LMPRT, may reduce the rate of missed diagnoses. Purpose: The primary objectives of this study were to evaluate the incidence of and risk factors for lateral meniscus root lesions in a large series of patients undergoing anterior cruciate ligament (ACL) reconstruction. Study Design: Case-control study; Level of evidence, 3. Methods: All patients who underwent primary or revision ACL reconstruction by a single surgeon between January 2011 and April 2018 were considered for study eligibility. From this overall population, all patients who underwent repair of an LMPRT were identified. The epidemiology of LMPRT was defined by the incidence within the study population, stratified by key demographic parameters. Potentially important risk factors for the presence of LMPRT were evaluated in multivariate logistic regression analysis. Results: A total of 3956 patients undergoing ACL reconstruction were included in the study. An LMPRT was identified and repaired in 262 patients (6.6%). Multivariate analyses demonstrated that significant risk factors for LMPRT included a contact sports injury mechanism (7.8% incidence with contact sport mechanism vs 4.5% with noncontact mechanism; odds ratio, 1.69; 95% CI, 1.266-2.285; P < .001) and the presence of a medial meniscal tear (7.9% incidence with medial meniscal tear vs 5.8% without; odds ratio, 1.532; 95% CI, 1.185-1.979; P < .001). Although the incidence of LMPRT in male patients (7.3%) was higher than in females (4.8%), this was not significant in multivariate analysis ( P = .270). Patient age, revision ACL reconstruction, and a preoperative side-to-side laxity difference ≥6 mm were not significant risk factors for LMPRT. Conclusion: The incidence of LMPRT was 6.6% in a large series of patients undergoing ACL reconstruction. Participation in contact sports and the presence of a concomitant medial meniscal tear were demonstrated to be important independent risk factors. Their presence should raise the index of suspicion for this injury pattern.